End-expiratory lung volume recovers more slowly after closed endotracheal suctioning than after open suctioning: A randomized crossover study - Corley, Amanda; Spooner, Amy J.; Barnett, Adrian G.; Caruana, Lawrence R.; Hammond, Naomi E.; Fraser, John F. (Journal of critical care)
Endotracheal suctioning causes significant lung derecruitment. Closed suction (CS) minimizes lung volume loss during suction, and therefore, volumes are presumed to recover more quickly postsuctioning. Conflicting evidence exists regarding this. We examined the effects of open suction (OS) and CS on lung volume loss during suctioning, and recovery of end-expiratory lung volume (EELV) up to 30 minutes postsuction. Randomized crossover study examining 20 patients postcardiac surgery. CS and OS were performed in random order, 30 minutes apart. Lung impedance was measured during suction, and end-expiratory lung impedance was measured at baseline and postsuctioning using electrical impedance tomography. Oximetry, partial pressure of oxygen in the alveoli/fraction of inspired oxygen ratio and compliance were collected. Reductions in lung impedance during suctioning were less for CS than for OS (mean difference, −905 impedance units; 95% confidence interval [CI], −1234 to –587; P < .001). However, at all points postsuctioning, EELV recovered more slowly after CS than after OS. There were no statistically significant differences in the other respiratory parameters. Closed suctioning minimized lung volume loss during suctioning but, counterintuitively, resulted in slower recovery of EELV postsuction compared with OS. Therefore, the use of CS cannot be assumed to be protective of lung volumes postsuctioning. Consideration should be given to restoring EELV after either suction method via a recruitment maneuver.